2019
DOI: 10.1007/s40258-019-00528-w
|View full text |Cite
|
Sign up to set email alerts
|

Cost-utility Analysis of Opportunistic and Systematic Diabetic Retinopathy Screening Strategies from the Perspective of the Brazilian Public Healthcare System

Abstract: Objective To perform a cost-utility analysis of diabetic retinopathy (DR) screening strategies from the perspective of the Brazilian Public Healthcare System. Methods A model-based economic evaluation was performed to estimate the incremental costs per quality-adjusted life-year (QALY) gained between three DR screening strategies: (1) the opportunistic ophthalmology referral-based (usual practice), (2) the systematic ophthalmology referral-based, and (3) the systematic teleophthalmology-based. The target popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 44 publications
(67 reference statements)
0
25
0
2
Order By: Relevance
“…Ben et al [26] performed a model-based economic evaluation to compare three DR screening practices in Brazil. The population included were patients with type 2 DM aged 40 years and without known DR.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ben et al [26] performed a model-based economic evaluation to compare three DR screening practices in Brazil. The population included were patients with type 2 DM aged 40 years and without known DR.…”
Section: Resultsmentioning
confidence: 99%
“…Kanjee et al [25] demonstrated a lower cost to the telemedicine program compared to the conventional in-clinic screening in a Canadian cohort. Ben et al [26] presented that systematic teleophthalmology based screening is cost-effective compared to opportunistic ophthalmology-referral based screening in Brazil. Stanimirovic et al [27] found that teleophthalmology screening dominated the standard of care in a Canadian pilot study (ICER < 0).…”
Section: Discussionmentioning
confidence: 99%
“…The sustainability and cost-effectiveness of screening programs are also fundamental for its implementation and success; to the best of our knowledge, ours is the first report on the performance of low-cost, portable handheld devices for DR screening in an urban setting in Brazil, a continent-sized country with very heterogeneous socioeconomic realities and an uneven distribution of ophthalmologists [17], home to the fifth biggest diabetic population in the world [18] and also to the largest public free and chronically underfinanced healthcare system [19]. Multiple socioeconomic barriers prevent access to eye examination in the poor regions of Brazil [3]. Recently, several authors have proposed teleophthalmology to increase access in Brazil and elsewhere, with favorable cost-effectiveness results and a reduced burden to specialized services [3,16,17], in both geographically isolated [15] and highly urbanized areas [20].…”
Section: Discussionmentioning
confidence: 95%
“…Diabetic retinopathy (DR) is a leading cause of severe visual loss which affects approximately 30 million individuals worldwide and can be prevented with timely screening, detection and treatment; however, even in high-income countries, access to yearly eye examinations is limited to only one-third to one-half of adults with diabetes, leaving a substantial number of patients at risk [1]. In the USA, only about 60% of people with diabetes have recommended yearly screenings for diabetic retinopathy; in some community-based studies, that rate is even lower [2]; in middle-to low-income countries, where access to ophthalmic care is generally limited, the rate of individuals with diabetes who have access to eye examinations is remarkably low [3]. In Brazil, primary health care is developed through forms of teamwork composed of a physician, a nurse, nursing assistants and community agents of health, aiming to assist populations defined by basic health units ("Unidade Básica de Saúde"-UBSs).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple socioeconomic barriers prevent access to eye examination in the poor regions of Brazil [2]. Recently, several authors have proposed teleophthalmology to increase access, with favorable cost-effectiveness results and a reduced burden to specialized services [13,16].…”
Section: Discussionmentioning
confidence: 99%